2022
DOI: 10.1371/journal.pone.0262856
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial tendency across the adult lifespan

Abstract: This study examines whether age associates with entrepreneurship tendencies across the lifespan, after taking into account aspects of personality that affect entrepreneurship. Participants (N = 963) aged 18–81, including 200 actual entrepreneurs, completed questionnaires about entrepreneurship tendency, personality traits, and attachment orientations. Results show that age is associated with a reduced tendency to engage in entrepreneurial activity. However, this decline is quite limited, it weakens with age, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Moreover, it may facilitate the development of networks and the ability to pitch and sell ideas (Bazkiaei et al, 2020). Furthermore, a recent study on a sample of wide age groups also reported a positive relationship between extraversion and entrepreneurial tendencies (Zelekha & Kavé, 2022). Therefore, we propose that:…”
Section: Extraversionmentioning
confidence: 85%
“…Moreover, it may facilitate the development of networks and the ability to pitch and sell ideas (Bazkiaei et al, 2020). Furthermore, a recent study on a sample of wide age groups also reported a positive relationship between extraversion and entrepreneurial tendencies (Zelekha & Kavé, 2022). Therefore, we propose that:…”
Section: Extraversionmentioning
confidence: 85%